OPTIMALISASI RAWA MAYO SEBAGAI SUMBER AIR DI KAWASAN KUMBE - KURIK DENGAN SISTEM POMPANISASI DI KABUPATEN MERAUKE - , Dominikus Catus B, ST. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Mayo Swamp so far is used for irrigating the agriculture area of Kampung Kurik II (Harapan Makmur), Kampung Kurik (Wonorejo) and Kampung Kurik I (Rawasari). The benefit of Mayo Swamp water source is hoped to answer the demand of water irrigation towards the potency of areaâs width. Research is needed to be conducted first in order to get the maximal benefit of the accommodated water in Mayo Swamp for irrigation water supply area which of width is 2038Ha. In this research, some shifted schedule and planting pattern is done in order to maximize the area potency and the available swamp water. The three alternative which simulated based on the planting schedule include Alternative I which is started in January, while Alternative II and Alternative III are started in November and December with the planting pattern Rice plant-Rice plant-Seasonal Plants. The best decided alternative is determined by using the method Analytical Hierarchy Process (AHP) by considering the sufficiency factor which is represented by the indicator of Relative Irrigation Supply (RIS), while efficiency and effectiveness are represented by the efficiency system (Esistem) and planting intensity (IT). The priority determination (the best alternative) is done by choosing the biggest weight from the three planned alternatives. Based on the method Analytical Hierarchy Process (AHP), the three alternative are conducted by considering the planting schedule which refers to the factor of areaâs width, water efficiency, and planting intensity. The most ideal planting schedule based on AHP has to be conducted in November. In the planting width of the first alternative on MT-I, MT-II and MT III is 236 Ha, while on the second and third alternative of planting width on MT-III (seasonal plants) are 50 Ha and 75 Ha. Referring to the second and third alternative then the planting width of MT-I and MT-II are 316 Ha and 306 Ha. The pump which is used to irrigate the farmersâ rice fields includes 2 units of pump machines with the capacity 0.75 m3/sec with the duration of optimal operation approximately 7 hours/day.